Effects of introducing Type&Screen system on rational use of transfusions - Stefanović Aleksandar O.; Čolak Emina S.; Stanojević Gordana D.; Nikolić Ljubinka I. (Hospital Pharmacology, 2021)
Introduction: The number of blood donors at the global level has decreased primarily due to ethical and age-related changes in the structure of the planet's population. In addition, there is over ordering of blood for surgical patients. Accordingly, there is a need for rationalizing the testing i.e. reducing the number of cross-matchings and decrease in the use of blood. A type and screen (T&S) upon admission is sufficient for most patients. Determination of ABO blood group and Rh type, and screens for clinically significant alloantibodies is denoted as type and screen (T&S). Aim: Comparison of pharmaco-economic effect using transfusion indices on the number of performed cross-matches and the amount of packed red blood cells issued. Material and Methods: The authors present the comparison between the year 2010 before the introduction of the Type and Screen (T&S) system and the year 2019 when the T&S system and restrictive policy in transfusion practice, were introduced. Data for 2010 were collected from written transfusion protocols of the clinic, and for 2019 were obtained from the hospital information system (Heliant) and written transfusion protocols. The difference between two groups of data was examine with Chi-square test and Fisher exact test, with the reliability level set at p<0.05. Results: With the introduction of the T&S system, the number of cross-matches was reduced from 0.63 to 0.49 and the number of blood units was reduced from 0.21 to 0.11 per hospitalized patient, which at the level of one clinic represents a significant pharmacoeconomic contribution of approximately 50%. In our study, after processing T&S in ordering of blood, the indices (CTR, %T, TI) failed to improve. Despite of unsatisfactory transfusion indices, the application of restrictive indication policies in accordance with national and international guidelines has led to highly significant reduction in the consumption of total blood from 3243 to 1867 blood units. The BOQ as an overall assessment of the results after the introduction of the T&S procedure indicated improvement. Conclusions: The introduction of validation in blood transfusion indirectly draws the attention of prescribing physicians to take into account the significance of blood therapy. The effects of the introduction of the T&S method and restrictive transfusion policy are savings in blood consumption, decreased number of patients tested, a significant reduction in used blood units, and the number of performed cross-matches, despite the increased number of patients.